Monoterpenoid Coumarins from the Peels of Clausena lansium - Deng, Hui-Dong; Mei, Wen-Li; Guo, Zhi-Kai; Liu, Shuai; Zuo, Wen-Jian; Dong, Wen-Hua; Li, Shao-Peng; Dai, Hao-Fu (Planta Medica, 2014)
A phytochemical investigation on the peels of Clausena lansium (Lour.) Skeels led to the isolation of two new monoterpenoid coumarins, named clauslactone V (1) and clauslactone W (2), together with three known analogues (3–5). Their structures were elucidated by spectroscopic techniques (UV, IR, MS, 1D and 2D NMR). All the compounds were evaluated for hypoglycemic activity, and compounds 1–5 showed α-glucosidase inhibitory activity in vitro.
Keywords: Clausena lansium; Rutaceae; monoterpenoid coumarins; clauslactone V; clauslactone W; hypoglycemic activity